Vlogging in teaching and learning during pandemic / Surina Nayan, Majdah Chulan and Fazmawati Zakaria - Nayan, Surina; Chulan, Majdah; Zakaria, Fazmawati (Universiti Teknologi MARA, Perlis, 2022)
This is a conceptual paper on the use of vlog in the context of teaching and learning during Covid 19 in Malaysia. Many industries ranging from tourism, aviation, fishery and food manufacturing are affected by the Covid 19 pandemic. Not excluding is the education sector which is also badly hit by this pandemic. People were panicked at first. However, now people are in the process of adapting and adopting to the new norm which requires them to follow some preventive measures to prevent virus contraction. Education sector is one of the sectors that is badly affected by this pandemic. Educationists and academicians are trying their best to impart knowledge to learners despite having challenges. One of the ways to ensure learning takes place through the online distance learning (ODL) is by using vlog. Vlogging has many benefits as learners can access it anywhere any time. Learning and teaching will be easier as learners can control their own learning environment. Vlogs can also improve learners' engagement and boost motivation. Learners are able to use their skills to share their work with others through vlogging. Images used in vlogs also help learners to engage more in their learning. Despite many advantages of using vlog in online teaching and learning, there are some disadvantages of it such as learners' learning progress is difficult to be monitored, internet connection problem and it does not allow immediate and sufficient feedback.